Mange-mite infestation in small ruminants in Ethiopia: Systematic review and meta-analysis - Asmare, K.; Abebe, R.; Sheferaw, D.; Krontveit, R.I.; Wieland, Barbara (Elsevier, 2016)
Mange-mites are economically important ectoparasites of sheep and goats responsible for rejection or downgrading of skins in tanneries or leather industries in Ethiopia. The objective of this systematic review was to compute the pooled prevalence estimate and identify factors influencing mange-mite prevalence in sheep and goats at national level based on the available research evidence. Articles on mange-mite infestation of small ruminants in Ethiopia were searched in PubMed, Web of Science, Google scholar and African journals on-line. The review was based on 18 cross-sectional studies carried out between 2003 and 2015 in four administrative states of Ethiopia. Accordingly, the pooled prevalence estimate in a random effects meta-analysis was estimated to be 4.4% (95% CI 3.0, 6.3) although there were evidence of a substantial amount of between-study variance (I2 = 98.4%). In subgroup and multivariable meta-regression analyses, animal species, agro-ecology and administrative state were found to have significant effect on the prevalence estimate (P < 0.05) and explained 29.78% of the explainable proportion of the heterogeneity noted between studies The prevalence was found to be higher in goats in lowland agro-ecology. Region wise the highest estimate was calculated for Amhara (6.4%) followed by Oromia (4.7%), Tigray (3.6%) and Southern Nations, Nationalities and People Region (SNNPR) (3.1%). Significant difference was noted between Amhara and SNNPR. The study further revealed that mites of the genus Sarcoptes, Demodex and Psoroptes are the most prevalent mites infesting small ruminants in Ethiopia. Valid studies were lacking from five regional states. As some of these regions are known for their large small ruminant population, further studies are warranted to produce better picture of the infestation at a national level. Meanwhile, the need for monitoring the ongoing control intervention is suggested.